Evaluasi Pembelajaran Daring Pada Jurusan Akuntansi Politeknik Negeri Padang - Yentifa, Armel; Frima, Rini (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research evaluates the online learning system that has been carried out by the accounting department of PNP. Lecturers and students of the accounting department of PNP become the subject of this research. This research used a descriptive qualitative approach where the data collected through questionnaires and Forum Group Discussion (FGD). The results showed that 18% of students do not have a PC/laptop. This situation makes the students difficult to take online learning because they have to take computer application courses every semester. Hence, there are 9% of students who lived in remote areas, which requires them to find internet network spots that are far from their house. This research found that students like the asynchronous learning system better than the synchronous learning system. About 15.8% of lecturers in the Accounting Department of PNP feels that it is hard to prepare teaching materials for online learning. And 21.1% of lecturers also have a problem with using the Learning Management System (LMS).